False-negative MRI breast screening in high-risk women. Issue 3 (March 2017) - Maxwell, A.J.; Lim, Y.Y.; Hurley, E.; Evans, D.G.; Howell, A.; Gadde, S.
Abstract : Aim: To determine the frequency of and reasons for false-negative breast magnetic resonance imaging (MRI) examinations in high-risk women undergoing annual screening. Materials and methods: The family history clinic database was interrogated and women at high risk of breast cancer who had undergone screening MRI and been diagnosed with breast cancer within 2 years of the MRI examination were identified. All available MRI examinations were reviewed and classified by two radiologists. Results: Of 32 women diagnosed with breast cancer, 23 had MRI images available for review. Fourteen were diagnosed at MRI, four at interim mammography, two symptomatically, one incidentally on ultrasound, and two at risk-reducing mastectomy. Ten women (43%) had potentially avoidable delays in diagnosis. The preceding MRIs were classified as false-negative screens in five women (one prevalent, four incident), false-negative assessment in seven and minimal signs in three (three women were assigned dual classifications). Common reasons for diagnostic delay included small enhancing masses that were overlooked, areas of non-mass enhancement that showed little or no change between screens, false reassurance from normal conventional imaging at assessment, and overreliance on short-interval repeat MRI. Conclusion: Small enhancing foci, masses, and areas of segmental non-mass enhancement are common MRI features of early breast cancer. Lack of change of non-mass enhancement on serial examinations does not exclude malignancy. Double reading of both screening and assessment examinations is recommended. Ready access to MRI biopsy is essential. Short-interval repeat MRI should be limited to reassessing low suspicion areas likely to be benign glandular enhancement. Annual mammography remains important in these women. Highlights: Subtle abnormalities at the cancer site on preceding MRIs are common. Lack of change of non-mass enhancement does not exclude malignancy. Double reading of MRI screening and assessment is recommended. Short interval repeat MRI has only a limited role. Ready access to MRI-guided biopsy is essential.